Trade Costs, Market Integration, and Macroeconomic Volatility - Naknoi, Kanda (IMF Working Papers; Working Paper ;, 2003)
This paper examines the effects of trade costs on macroeconomic volatility. We first construct a dynamic, two-country general equilibrium model, where the degree of market integration depends directly on trade costs (transport costs, tariffs, et cetera). The model is a extension of Obstfeld and Rogoff (1995). Naturally, a reduction in trade costs leads to more market integration, as the relative price of foreign goods falls and households increase their consumption of imported goods. In addition, with more market integration, the model predicts that the variability of the real exchange rate should fall, while the variability of the trade balance should increase. Trade costs have ambiguous effects on the volatility of other macro variables, such as income and consumption. Finally, we present some empirical findings that provide mixed support for the model's predictions.